Measuring cognitive complexity in parametric design. Issue 3 (3rd July 2019) - Lee, Ju Hyun; Ostwald, Michael J.
ABSTRACT: Cognitive complexity is a psychological concept that is used to analyse different approaches to problem solving, activity prioritising, information clustering and abstraction. This paper develops a combined approach utilising protocol analysis and linkography to measure the cognitive complexity of parametric design processes. The approach is selectively applied and tested using pilot data from two experiments in parametric modelling environments. The results indicate that: (i) levels of design cognition can explain individual cognitive complexity and (ii) sequential entropies over time can be regarded as quantitative measures of complexity. Decile growth plots of linkographs are used to reveal individual cognitive differences in the design process. This approach contributes to advancing fundamental knowledge about design cognition and complexity.